2003
DOI: 10.3892/ijmm.11.4.535
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of fluoxetine enantiomers in mammalian neural and cardiac tissues

Abstract: Abstract. Racemic fluoxetine is a widely used SSRI antidepressant compound having also anticonvulsant effect. In addition, it was shown that it blocked several types of voltage gated ion channels including neural and cardiac calcium channels. In the present study the effects of enantiomers of fluoxetine (R(-)-fluoxetine and S(+)-fluoxetine) were compared on neuronal and cardiac voltage-gated Ca 2+ channels using the whole cell configuration of patch clamp techniques, and the anticonvulsant action of these enan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 38 publications
3
18
0
Order By: Relevance
“…15,[30][31][32] These contradictory effects may be explained by species differences in electrophysiological properties. For example, action potential prolongation by inhibition of I Kr is clearly species-dependent, as shown in simulations and experimental studies.…”
Section: Discussionmentioning
confidence: 99%
“…15,[30][31][32] These contradictory effects may be explained by species differences in electrophysiological properties. For example, action potential prolongation by inhibition of I Kr is clearly species-dependent, as shown in simulations and experimental studies.…”
Section: Discussionmentioning
confidence: 99%
“…The major cause of the higher mortality rate in psychiatric patients versus the general population is sudden cardiac death, which mainly results from arrhythmias that occur during treatments with psychotropic drugs. It has been reported that fluoxetine decreases the maximum rate of rise of the depolarization phase (V max ) of ventricular cell preparations Magyar et al, 2003), but little is known about the direct effect of fluoxetine on the biophysical properties of Na v 1.5.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, the pure isomer was even shown to provide an advantage in the clinical use of a compound administered in the form of racemate so far (e.g. Valenzuela et al 1995;Stoschitzky et al 2001;Magyar et al 2003;Eap et al 2007;Wang et al 2008). Thus, it might be beneficial to produce and test the pure S-isomer of 444 if this compound was considered to be used in the clinical practise in the future.…”
Section: Discussionmentioning
confidence: 99%